Irrational Denominators

Algebra Level 2

1 1 + 2 + 1 2 + 3 + 1 3 + 4 + + 1 8 + 9 = ? \frac{1}{ 1 + \sqrt{2} } + \frac{1}{ \sqrt{2} + \sqrt{3} } + \frac{1}{ \sqrt{3} + \sqrt{4} } + \ldots + \frac{1}{ \sqrt{8} + \sqrt{9} } = \text{ ?}


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Sakanksha Deo
Mar 10, 2015

1 1 + 2 + 1 2 + 3 + 1 3 + 4 + . . . . . . . . . . + 1 8 + 9 \frac{1}{ 1 + \sqrt{2} } + \frac{1}{ \sqrt{2} + \sqrt{3} } + \frac{1}{ \sqrt{3} + \sqrt{4} } + .......... + \frac{1}{ \sqrt{8} + \sqrt{9} }

= 2 1 ( 2 ) 2 1 + 3 2 ( 3 ) 2 ( 2 ) 2 + . . . . . . . . + 9 8 ( 9 ) 2 ( 8 ) 2 = \frac{ \sqrt{2} - 1 }{ ( \sqrt{2} )^{2} - 1 } + \frac{ \sqrt{3} - \sqrt{2} }{ ( \sqrt{3} )^{2} - ( \sqrt{2} )^{2} } + ........ + \frac{ \sqrt{9} - \sqrt{8} }{ ( \sqrt{9} )^{2} - ( \sqrt{8} )^{2} }

= 2 1 + 3 2 + 4 3 + . . . . . . . . . + 9 8 1 = \frac{ \sqrt{2} - 1 + \sqrt{3} - \sqrt{2} + \sqrt{4} - \sqrt{3} + ......... + \sqrt{9} - \sqrt{8} }{1}

= 9 1 = 3 1 = 2 = \sqrt{9} - 1 = 3 - 1 = \boxed{2}

Great Solution!

Aryan Gaikwad - 6 years, 3 months ago

Log in to reply

Thanxx...... 😊

Sakanksha Deo - 6 years, 3 months ago
Caeo Tan
Sep 13, 2015

You can make it as a summation (like the one below):

sum(n)(start=1, end=8) [1/(sqrt(n)+sqrt(n+1))]

=sum(n)(start=1, end=8) [1/(sqrt(n)+sqrt(n+1))]*[(sqrt(n)-sqrt(n+1))/(sqrt(n)-sqrt(n+1))]

=sum(n)(start=1, end=8) (sqrt(n)-sqrt(n+1))/(n-(n+1))

=sum(n)(start=1, end=8) [ -(sqrt(n)-sqrt(n+1))]

=sum(n)(start=1, end=8) [-sqrt(n)+sqrt(n+1)]

=-1+sqrt(2)-sqrt(2)+sqrt(3)-sqrt(3)+sqrt(4)...-sqrt(8)+sqrt(9)

=-1+sqrt(9)

=-1+3

=-2 (final answer)

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...